(untitled) (Pengelolaan Sumberdaya Pembangunan, 2021)
According to Article 1 point 1 of Law Number 39 of 2009 concerning Special Economic Zones, it is stated that the Special Economic Zones, hereinafter referred to as KEK, are areas with certain boundaries within the jurisdiction of the Unitary State of the Republic of Indonesia designated to carry out economic functions and obtain certain facilities. . In recent years, the government has made policies to increase investment, accelerate development, especially outside Java and increase economic competitiveness through the development of Special Economic Zones (KEK), Industrial Estates (KI) and National Tourism Strategic Areas (KSPN). The legal basis for the formation of KEK is Law Number 39 of 2009 concerning Special Economic Zones, Government Regulation Number 96 of 2015 concerning Facilities and Facilities in KEK and Regulation of the Minister of Finance Number 104 / PMK.010 / 2016 concerning Tax, Customs and Excise Treatment in KEK . One of the conditions that must be met by a region to manage a special economic sector is that a development and management business entity must be formed, therefore in 2016 the local government issued a decree for the governor of North Sulawesi province number 6 of 2016 concerning the establishment of PT. Building a great sulut regional company which was later appointed as a Regional Owned Enterprise that manages the Bitung Special Economic Zone. Furthermore, until 2019, PT Pembangunan Sulut Hebat as the manager of the Bitung SEZ has only controlled 92 hectares of land (still under the control of the North Sulawesi Provincial Government) of the 441 hectares that are included in the Bitung SEZ. Keywords: Policy Implementation, KEK, Bitung City, Economy.